2021
DOI: 10.3389/fimmu.2021.712688
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Specific Sex Effects on Susceptibility to Infectious Diseases

Abstract: Inflammation is an integral part of defense against most infectious diseases. These pathogen-induced immune responses are in very many instances strongly influenced by host’s sex. As a consequence, sexual dimorphisms were observed in susceptibility to many infectious diseases. They are pathogen dose-dependent, and their outcomes depend on pathogen and even on its species or subspecies. Sex may differentially affect pathology of various organs and its influence is modified by interaction of host’s hormonal stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 117 publications
(201 reference statements)
0
10
1
Order By: Relevance
“…This is higher than the ratio of 1.28:1 found in a previous study from China, where the percentage of female patients was 43.8% 1 . Gender plays an important role in immune responses, including susceptibility to fungal infections, possibly due to sex‐specific genetic architecture, sex‐differentiated responses to disease susceptibility may be caused by direct and indirect effects of sex hormones as well as non‐hormonally biased effects of the X and Y chromosomes 23 …”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This is higher than the ratio of 1.28:1 found in a previous study from China, where the percentage of female patients was 43.8% 1 . Gender plays an important role in immune responses, including susceptibility to fungal infections, possibly due to sex‐specific genetic architecture, sex‐differentiated responses to disease susceptibility may be caused by direct and indirect effects of sex hormones as well as non‐hormonally biased effects of the X and Y chromosomes 23 …”
Section: Discussioncontrasting
confidence: 58%
“…1 Gender plays an important role in immune responses, including susceptibility to fungal infections, possibly due to sex-specific genetic architecture, sex-differentiated responses to disease susceptibility may be caused by direct and indirect effects of sex hormones as well as nonhormonally biased effects of the X and Y chromosomes. 23 Kerion caused by zoophilic pathogens is reported more common in children than in adults; 24 Wang et al 24 reported that the incidence of kerion in childhood was 13.9% (10/72), which was significantly higher than that in adults (3.8%, 4/104). In our study, grey patch (59%, 75/127) was the most common, followed by kerion ( cohort, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression of IgG2b among females in mice and IgG2 in humans may help explain why females often fare better than males when vaccinated or when exposed to viruses such as influenza and SARS-CoV-2 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. In the context of COVID-19, IgG2 assists the reduction of antibody dependent enhancement (ADE) and the modulation of immune pathologies [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Females often mount better immune responses compared to males toward vaccines and viruses including influenza virus and SARS-CoV-2 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Estrogen plays a key role in protection [ 20 , 24 , 32 ], as was demonstrated by an improvement in vaccine responses when supplemental estrogen was administered to ovariectomized mice [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows that the risk of boys suffering from childhood stunting is 1.07 times that of girls, the same as many results from China ( 20 , 21 , 39 , 40 ) and other regions ( 41 , 42 ), probably due to the interaction of biological and socio-cultural factors. We also found differences between boys and girls in growth trajectories and immune function beginning prenatally ( 43 , 44 ). Caregivers treat children of different genders differently ( 45 47 ).…”
Section: Discussionmentioning
confidence: 63%